Risk And Return Model of Digital Cryptocurrency Asset Investment In Indonesia - Rico Nur Ilham; Isfenti Sadalia; Nisrul Irawati; Irada Sinta (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Cryptocurrency is an investment commodity that can generate returns and already has a license to be traded in exchange trading through the Indonesian Commodity Futures Trading Regulatory Agency (BAPEPTI). There are quite a lot of crypto digital assets traded in Indonesia through the trading company Indodax. The purpose of this research is focused on formulating a risk management process in cryptocurrency digital asset investment. In addition, from the results of this study, a policy recommendation known as LCTR or "Legal Cryptocurrency and Tax Revenue" is expected to be considered by the government in formulating policies on crypto digital assets so that the interests of all parties can be accommodated for the realization of maximum state revenue from commodity trading. crypto digital assets. This type of research is quantitative descriptive with the research population, namely 5 cryptocurrency coins with the largest market caps in Indonesia, namely Bitcoin, Ethereum, Ripple, Bitcoin Cash, Litecoin in Indonesia. The type of data in this study is time series data taken from March 2021 to December 2021 by conducting a documentation study conducted on the publication of monthly cryptocurrency transaction reports, so that a target population of 240 (4 years x 12 months x 5 coins) monthly report data is obtained. for the research sample. The data analysis method in this study used multiple linear regression and data analysis used statistical software e-views version 10. The output of this study was the publication of reputable international journals,